Development of mechanobiomimetic strategies to drive stem cell behaviour for bone regeneration - EICHHOLZ, KIAN (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2019)
There are a host of cases where clinical intervention must be taken to treat diseased or damaged bone, including severe fractures, defects, tumours requiring tissue removal, and debilitating diseases such as osteoporosis. However, there are no current treatments which adequately achieve this goal, with current autografting approaches having severe limitations in terms of quantity of tissue available and additional surgical sites which damage healthy tissue and increase infection risk. There is thus a need to develop new strategies for bone regeneration. Understanding the mechanisms behind bone regeneration, and in particular, the key role of the mesenchymal stem cell (MSC) in this process, would provide invaluable information for the development of strategies to effectively regenerate bone in a physiologically appropriate manner. The overall aim of this thesis was to investigate the biophysical cues within the stem cell niche in bone which drive the recruitment and osteogenesis of MSCs, with the aim of developing strategies to recapitulate this behaviour and guide bone repair. The two primary means by which MSC behaviour is mediated were investigated in this thesis: indirect biophysical cues from osteocytes (stream 1 – chapter 3), and direct biophysical cues from the underlying fibrous tissue (stream 2 – chapter 4-6), which were subsequently combined to create a mechano-biomimetic scaffold for bone regeneration (chapter 7). In this thesis, the indirect biophysical cues from osteocyte signalling to MSCs were first investigated (chapter 3), where osteocytes were shown to release distinct mechanically activated osteocyte-derived extracellular vesicles (MAEVs) which contained unique cargo compared to extracellular vesicles (EVs) from statically cultured cells. These MAEVs significantly enhanced MSC recruitment and osteogenesis, with trends being almost identical to MSCs treated with conditioned medium from mechanically stimulated osteocytes. This confirmed that EVs are a key component in osteocyte-MSC mechanosignaling, and reveals their potential alone for use as mechanotherapeutics to guide regeneration. Next, the role of direct biophysical cues in mediating MSC behaviour was investigated. To facilitate this, a melt electrowriting (MEW) printer was designed and built (chapter 4) to facilitate the fabrication of defined fibrous microenvironments upon which to study MSC behaviour. Various architectures with 10 μm fibre diameter were fabricated, where it was demonstrated that a 90° architecture enhanced MSC spreading and Yesassociated protein (YAP) nuclear expression, a marker for osteogenesis (chapter 5). Long term culture of MSCs further revealed enhanced osteogenic differentiation in this scaffold architecture. The role of mineral modifications in driving MSC osteogenesis was further investigated (chapter 6). A biomimetic nano-needle hydroxyapatite (nnHA) coating was developed, characterised and compared to other mineral modification methods, including a commonly used coating method which yields a micro-plate hydroxyapatite (pHA) morphology, and a composite polycaprolactone-hydroxyapatite material to fabricate fibres with incorporated mineral. The nnHA coating significantly enhanced MSC mineralisation compared to all other groups and was also shown to facilitate a more controlled release of BMP2, demonstrating its potential for use in applications requiring controlled drug release. Finally, stream 1 and 2 were combined, with MAEVs being used for the functionalisation of nnHA scaffolds (chapter 7). The addition of MAEVS further significantly enhanced mineralisation almost 2-fold, in addition to a total 24-fold compared to the 90° scaffold developed in chapter 4 and a total of 52-fold compared to random fibrous scaffolds. This biomimetic scaffold which incorporates both direct and indirect biophysical cues inspired by the native stem cell niche in bone thus holds great potential as a more physiologically relevant and effective strategy to guide bone regeneration.
APPROVED
Keywords: bone; tissue engineering; tissue regeneration; MEW; melt electrowriting; EV; extracellular vesicle; mechanobiology; MSC; stem cell; osteocyte